2009
DOI: 10.1124/dmd.109.027821
|View full text |Cite
|
Sign up to set email alerts
|

The Glycogen Synthase Kinase Inhibitor 3-(2,4-Dichlorophenyl)-4-(1-methyl-1H-indol-3-yl)-1H-pyrrole-2,5-dione (SB216763) Is a Partial Agonist of the Aryl Hydrocarbon Receptor

Abstract: ABSTRACT:Kinase inhibitors are frequently used tools in signal transduction research. 3-(2,4-Dichlorophenyl)-4-(1-methyl-1H-indol-3-yl)-1H-pyrrole-2,5-dione (SB216763), a potent inhibitor of glycogen synthase kinase 3␤ (GSK3␤), is frequently used to activate ␤-catenin signaling by mimicking the action of Wnt molecules. ␤-Catenin is a crucial player in the regulation of hepatic drug metabolism. Thus, it is of particular importance to know whether the tools used to study the effects of ␤-catenin signaling may af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…This finding was confirmed in murine cells by analyses of AhR mRNA expression in Ctnnb1-mutated mouse liver tumors [37], cultured mouse hepatocytes [15,54,78], and mice with hepatocyte-specific knockout of Ctnnb1 [21,54]; see also Table 5. Moreover, preferential expression of the AhR in perivenous hepatocytes [15,79,80], which exclusively possess activated -catenin in healthy liver [14,81], supports the idea of a stimulatory role of -catenin in the regulation of AhR mRNA expression.…”
Section: Interaction With the Ahrsupporting
confidence: 67%
See 1 more Smart Citation
“…This finding was confirmed in murine cells by analyses of AhR mRNA expression in Ctnnb1-mutated mouse liver tumors [37], cultured mouse hepatocytes [15,54,78], and mice with hepatocyte-specific knockout of Ctnnb1 [21,54]; see also Table 5. Moreover, preferential expression of the AhR in perivenous hepatocytes [15,79,80], which exclusively possess activated -catenin in healthy liver [14,81], supports the idea of a stimulatory role of -catenin in the regulation of AhR mRNA expression.…”
Section: Interaction With the Ahrsupporting
confidence: 67%
“…Again similar to the AhR, PB-and TCPOBOP-induced levels of CAR target genes from phase I and phase II of drug metabolism (including the GST isoforms Gstm2, Gstm3, and Gstm6) were, for the most part, higher in wild type mice, as compared to their Ctnnb1 knockout counterparts (Table 3), indicating higher activity of CAR-dependent transcription in the presence of -catenin [21]. Of note, the induction of hepatocyte AhR mouse liver adenoma, Ctnnb1-mutated mRNA (cDNA microarray) [20,37] AhR mouse hepatocytes, Wnt3a mRNA (real-time RT-PCR) [15,54,78] AhR mouse hepatocytes, SB216763 mRNA (real-time RT-PCR) [15] AhR Ctnnb1 knockout mouse mRNA (real-time RT-PCR) [21,54] AhR mouse hepatocytes, SB216763 mRNA (real-time RT-PCR) [78] CAR Ctnnb1 knockout mouse mRNA (real-time RT-PCR) [21,36,88] CAR mouse liver adenoma, Ctnnb1-mutated mRNA (real-time RT-PCR) [36] CAR Ctnnb1 knockout mouse Protein (Western blotting) [88] PXR Apc knockout mouse mRNA (cDNA microarray) [14] PXR Ctnnb1 knockout mouse * mRNA (real-time RT-PCR) [21] PXR mouse hepatocytes, Wnt3a mRNA (real-time RT-PCR) [54] Arrows indicate up-or down-regulation of respective GST isoforms. *, in female mice only.…”
Section: Interaction With Carmentioning
confidence: 95%
“…7C). The latter observation is of special importance, since there are numerous small molecule inhibitors, which act as partial agonists of the AhR, e.g., U0126 (Andrieux et al, 2004) and SB216763 (Braeuning and Buchmann, 2009). Thus, it was necessary to prove that FH535 neither induces basal Cyp1a1 expression nor interferes with AhR agonist-mediated effects.…”
Section: Induction Of Ahr Target Genes In Mice With Ttr-cre-mediated mentioning
confidence: 97%
“…11) indicates that XAV could be a partial AHR agonist. This has been suggested for the GSK-3 inhibitor SB216763 (Braeuning and Buchmann, 2009). Also by the CYP1A induction pattern it is suggested that XAV (and possibly also AZP) could be a partial agonist for the AHR.…”
Section: Discussionmentioning
confidence: 86%